2014
DOI: 10.1080/10503307.2014.966346
|View full text |Cite
|
Sign up to set email alerts
|

Good-enough level and dose-effect models: Variation among outcomes and therapists

Abstract: Therapists should consider the rates of change for their own clients as well as by outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 31 publications
2
88
3
Order By: Relevance
“…Indeed, therapists account for approximately 5-10% of the variance in therapy outcomes, across a range of variables, such as general distress, symptom change, life-functioning, and client unilateral termination rates (e.g., Baldwin & Imel, 2013;Kraus, Castonguay, Boswell, Nordberg, & Hayes, 2011;Okiishi, Lambert, Nielsen, & Ogles, 2003;Owen, Adelson, Budge, Kopta, & Reese et al, 2014;Wampold & Brown, 2005). Imel, Sheng, Baldwin, and Atkins (in press) estimated that the best performing therapists (based on clients' reaching clinically and reliable change) would have assisted approximately seven times more clients as compared to the worst performing therapists over 10 years of their career.…”
Section: Therapist Effects In Psychotherapymentioning
confidence: 99%
“…Indeed, therapists account for approximately 5-10% of the variance in therapy outcomes, across a range of variables, such as general distress, symptom change, life-functioning, and client unilateral termination rates (e.g., Baldwin & Imel, 2013;Kraus, Castonguay, Boswell, Nordberg, & Hayes, 2011;Okiishi, Lambert, Nielsen, & Ogles, 2003;Owen, Adelson, Budge, Kopta, & Reese et al, 2014;Wampold & Brown, 2005). Imel, Sheng, Baldwin, and Atkins (in press) estimated that the best performing therapists (based on clients' reaching clinically and reliable change) would have assisted approximately seven times more clients as compared to the worst performing therapists over 10 years of their career.…”
Section: Therapist Effects In Psychotherapymentioning
confidence: 99%
“…Accordingly, there might be alternative models for trajectories of change for those who attend more than five sessions. Second, from the GEL studies, the rates of change significantly varied across clients (e.g., Baldwin et al, 2009;Owen, Adelson, Budge, Kopta, & Reese, 2014). This suggests that using the number of sessions as a moderator for clients' rate of change reflects only a part of the story.…”
Section: Dose Effect and Good-enough Level Modelsmentioning
confidence: 99%
“…Several studies have suggested that an alternative perspective, the good-enough level (GEL) model, better represents the nature of patient response to psychotherapy Barkham et al, 1996Barkham et al, , 2006Falkenstrom et al, 2016;Owen et al, 2016;Reese et al, 2011;Stiles et al, 2008Stiles et al, , 2015. According to the GEL model, patients who attend different lengths of treatment change at different rates; some respond quickly within a few sessions while others respond gradually with longer treatments.…”
Section: Introductionmentioning
confidence: 99%